2004
DOI: 10.1590/s0100-879x2004000400012
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of autonomic reflex control begins with cellular mechanisms at the first synapse within the nucleus tractus solitarius

Abstract: Visceral afferents send information via cranial nerves to the nucleus tractus solitarius (NTS). The NTS is the initial step of information processing that culminates in homeostatic reflex responses. Recent evidence suggests that strong afferent synaptic responses in the NTS are most often modulated by depression and this forms a basic principle of central integration of these autonomic pathways. The visceral afferent synapse is uncommonly powerful at the NTS with large unitary response amplitudes and depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 50 publications
0
42
0
Order By: Relevance
“…Increasing evidence from different laboratories, including our own, have shown that even within a relatively restricted group of nuclei, such as those comprised in the dorsal vagal complex, fundamental differences exists in the organization of synaptic circuits controlling GI, cardiovascular, and respiratory functions (1,3,6,14,15,17,18,24,29,45,51,52). This arrangement is quite logical, when considered from a physiological standpoint, since the requirements of each system vary greatly in the type, as well as the timing and duration, of responses.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence from different laboratories, including our own, have shown that even within a relatively restricted group of nuclei, such as those comprised in the dorsal vagal complex, fundamental differences exists in the organization of synaptic circuits controlling GI, cardiovascular, and respiratory functions (1,3,6,14,15,17,18,24,29,45,51,52). This arrangement is quite logical, when considered from a physiological standpoint, since the requirements of each system vary greatly in the type, as well as the timing and duration, of responses.…”
Section: Discussionmentioning
confidence: 99%
“…Neurons responsible for these homeostatic regulatory mechanisms are concentrated in the brainstem (Loewy, 1990;Guyenet, 2006) and actions in the brainstem are consistent with the substantial autonomic impact of propofol in humans (Ebert & Muzi, 1994;Ebert, 2005). Common to most of these reflex pathways is the nucleus of the solitary tract (NTS), the site of central terminations of visceral cranial afferent nerves (including the vagus) from the cardiovascular, respiratory and gastrointestinal systems (Saper, 2002;Andresen et al, 2004;Travagli et al, 2006;Guyenet, 2006). Arterial baroreceptors and respiratory afferents terminate within medial portions of the caudal NTS and are a source of excitatory glutamatergic input onto second-order NTS neurons (Mendelowitz et al, 1992;Doyle & Andresen, 2001; Kubin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Receptors in the cardiovascular system (intrinsic as well as extrinsic) detect changes in volume, pressure, flow, blood gases, pH, temperature, and movement and send peripheral information to the brain for neural processing. The nucleus tractus solitarius (NTS) in the dorsal brainstem is the primary termination site of cardiovascular afferents, and is critical in the regulation of baroreflex-mediated changes in the heart and peripheral vessels [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The above experimental evidence indicates that changes in baroreceptor reflex sensitivity and/or central resetting occur during and after exercise and following exercise training, and suggests the NTS as an important component in the central pathways. Although changes in synaptic transmission could occur in any central site within the baroreflex arc, the NTS was extensively studied because it is the first synaptic relay of sensory afferents in the central nervous system; it possesses a complex network of interconnected excitatory and inhibitory local and projecting neurons with multiple receptor types; and it plays a pivotal role in the integration of both viscerosensory and suprabulbar pathways in such a way that any local adjustment or modulation will be transmitted to many other nuclei and pathways, thus amplifying the effect [1,2,4,5,10,11,32,33]. Indeed, several studies indicate that NTS plays a major role in governing the sensitivity and setting point of baroreceptor function during pressure challenges either at rest, during exercise, or after exercise training [2,10,11,14••,15••,19,21,29,34].…”
Section: Introductionmentioning
confidence: 99%